2022
DOI: 10.2174/1389201022666210509022313
|View full text |Cite
|
Sign up to set email alerts
|

Current Overviews on COVID-19 Management Strategies

Abstract: The coronavirus pandemic has hit the world lately and caused acute respiratory syndrome in humans. The causative agent of the disease was soon brought to focus by scientists as SARS-CoV-2 and later called a novel coronavirus by the general public. Due to the severity and rapid spread of the disease, WHO classifies the COVID-19 pandemic as the 6th public health emergency even after taking efforts like worldwide quarantine and restrictions. Since only symptomatic treatment is available, the best way to control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 202 publications
0
9
0
Order By: Relevance
“…Since the launch of Target 2035 in 2019, we have witnessed the success of the open science model in the global fight against the COVID-19 pandemic. The swift sharing of SARS-CoV2 viral sequences 45 and other data has led to extraordinarily rapid development of new vaccines 46 and small molecule antiviral trials. 47–50 A recent example is the fast development of anti-viral small molecules against the SARS-CoV-2 protease, as part of an initiative called the COVID Moonshot.…”
Section: Future Outlookmentioning
confidence: 99%
“…Since the launch of Target 2035 in 2019, we have witnessed the success of the open science model in the global fight against the COVID-19 pandemic. The swift sharing of SARS-CoV2 viral sequences 45 and other data has led to extraordinarily rapid development of new vaccines 46 and small molecule antiviral trials. 47–50 A recent example is the fast development of anti-viral small molecules against the SARS-CoV-2 protease, as part of an initiative called the COVID Moonshot.…”
Section: Future Outlookmentioning
confidence: 99%
“…SARS-CoV-2 is included in the family COVID-19 viridae [58]. In addition, Table 1 proteins, spike (S), envelope (E), membrane (M), and 16 nonstructural proteins [1, 56,57,59,60] (Table 1). Attachment and internalization of the COVID-19 virus into the host is mediated by the presence of spikes on the virus surface (Fig.…”
Section: Comparative Analysis Between Dengue and Covid-19 Virus Life ...mentioning
confidence: 99%
“…When comparing the lifecycle of both the viruses (Fig. 2a and b), it is found that in the first phase of the COVID-19 virus life cycle, spike protein binds to the host cell ACE2 (angiotensin-converting enzyme 2) receptor [4,56,59,60,[62][63][64][65]. The first phase of the dengue virus life cycle binds to the heparan sulphate/DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) receptor present on the host cell with the help of protein E [22,41] (Table 1).…”
Section: Comparative Analysis Between Dengue and Covid-19 Virus Life ...mentioning
confidence: 99%
“…These drugs are broad-spectrum antivirals (remdesivir, lopinavir, ritonavir, arbidol, baloxavir marboxil, favipiravir), antiparasitic drugs (chloroquine, hydroxychloroquine, and ivermectin), immunomodulators (dexamethasone, tocilizumab, and interferon), antibiotics (azithromycin and doxycycline), and antitumor therapeutic (2-Deoxy-d-glucose, 2-DG) ( Andersen et al., 2020 ; Mesri and Lampidis, 2021 ). Besides antivirals, immunomodulators are aimed to block the cytokine storm in severe COVID-19, and neutralizing antibody cocktails have been employed to prevent subsequent virus entry ( Rai et al., 2021 ). Out of the abovementioned drugs, remdesivir and dexamethasone have shown promising clinical benefits in randomized controlled trials.…”
Section: Drug Target and Future Prospective Of Treatment For Severe Covid-19 With Gastrointestinal Manifestationsmentioning
confidence: 99%